Capital structure choice and company taxation: A meta-study - Lars P. Feld; Jost H. Heckemeyer; Michael Overesch (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2011)
This paper provides a quantitative review of the empirical literature on the tax impact on corporate debt financing. Synthesizing the evidence from 46 previous studies, we find that this impact is substantial. In particular, the tax rate proxy determines the outcome of primary analyses. Measures like the simulated marginal tax rate (Graham (1996a)) avoid a downward bias in estimates for the debt response to tax. Moreover, debt characteristics, econometric specifications, and the set of control-variables affect tax effects. Accounting for misspecification biases by means of meta-regressions, we predict a marginal tax effect on the debt ratio of 0.3.
Keywords: G30; H32; F23; 330; capital structure; corporate income tax; meta-analysis; Körperschaftsteuer; Steuerwirkung; Kapitalstruktur; Fremdkapital; Meta-Analyse; Welt